Ação do bioestimulante na cultura do maxixeiro (Cucumis anguria L.) sob condições de estresse salino - Souza Neta, Maria Lilia de (Universidade Federal Rural do Semi-Árido, 2016)
The objective of this work is to assess the effect of seeds treatment with biostimulant StimulateR on the gherkin crop, cv. Liso de Calcutá, under salt stress. The research was accomplished in three experiments, assessing the use of biostimulant on the seedlings, on the growth, fruits and seeds quality. The first experiment was accomplished in greenhouse of Ecological and Technological Department of UFERSA, assessing the gherkin seedlings quality under salt stress from seeds treatment with different biostimulant doses, using the completely randomized design, in factorial outline 2 x 5, with four repetitions. The first factor represents two salt levels of irrigation water (0,5 dS m-1 e 3,5 dS m-1) and the second one represents five doses of biostimulant applied by seed(0; 5; 10; 15 e 20 mL Kg-1), assessing emergence, emergence speed index, number of leaves, neck diameter, seedlings height, root length, root dry mass, aerial and total parts dry mass. The second experiment was conducted in experimental area belonging to the same department mentioned before, where the treatments were the same used in the first experiment, accomplished in subdivided parts with five repetitions, assessing the development and the fruit of anguria production whose seeds were treated and cultivated under salt stress conditions. We assessed the following variables: number of leaves and branches, dry mass of biggest branch length and leaves , stem, fruits and total dry mass, number, average mass and fruit production. On the third experiment, we assessed the physiological quality of seeds obtained in the previous experiment, developed in two phases, the first one in laboratory and the second one in greenhouse. We assessed humidity degree, seeds germination, first germination counting, accelerated aging test (with NaCl saturated solution). We also assessed emergence in greenhouse: emergence speed index, aerial parts dry mass and seedlings height. On the three experiments, the data obtained were analyzed from variance analysis, making the factors display for the variable that show significant answer to the interaction among the factors. In a general way, the data statistical analysis revealed significant effect from the interaction between the factors salinity and biostimulant for most variables assessed. In addition, the use of biostimulant was not efficient for most variables assessed. However, the biostimulant is efficient in order to maximize fruit production, regardless the quality of water used on irrigation, causing improvement on the quality of seeds obtained
Biostimulant action on culture in gherkin (Cucumis anguria L.) under salt stress
Keywords: Cucumis anguria L.; Salinidade; Regulador vegetal; Cucumis anguria L.; Salinity; Vegetal Regulator; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA